2014
DOI: 10.1021/cm502106v
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Co3O4 with Controlled Porosity: Inverse Micelle Synthesis and High-Performance Catalytic CO Oxidation at −60 °C

Abstract: Crystalline mesoporous cobalt oxides with improved catalytic activity in CO oxidation were synthesized using an inverse surfactant micelle method. The prepared materials are monodispersed nanoparticle aggregates, and the mesopores are formed by connected intraparticle voids. Powder X-ray diffraction (PXRD), N2 sorption, field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM) revealed that both pore and nanoparticle sizes are enlarged with increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
181
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(198 citation statements)
references
References 65 publications
14
181
0
Order By: Relevance
“…1 (c) and (d)) into account, the particles with a hexagonal thin platelet shape and a cubic shape, seen in Fig. 2 (c) [6][7][8][9][10]13,14) The present observed in situ oxidation by nitrate ions might become an efcient procedure to obtain further mixed valence functional metal oxide nanoparticles in one-pot process.…”
Section: Effect Of Cobalt Sources On Formation Of Co 3 O 4 Nanoparticlesmentioning
confidence: 75%
See 2 more Smart Citations
“…1 (c) and (d)) into account, the particles with a hexagonal thin platelet shape and a cubic shape, seen in Fig. 2 (c) [6][7][8][9][10]13,14) The present observed in situ oxidation by nitrate ions might become an efcient procedure to obtain further mixed valence functional metal oxide nanoparticles in one-pot process.…”
Section: Effect Of Cobalt Sources On Formation Of Co 3 O 4 Nanoparticlesmentioning
confidence: 75%
“…[1][2][3][4][5] Especially, tricobalt tetraoxide (Co 3 O 4 ), a mixed-valence transition metal oxide with spinel crystal structure, is regarded as one of the most promising p-type semiconducting materials for industrial and scienti c applications such as heterogeneous catalysts, [6][7][8][9][10][11][12] solid-state sensors, [13][14][15] magnetic materials, 16,17) and lithium ion rechargeable batteries. [18][19][20][21] Up to date, various types of preparation methods have been developed for the preparation of Co 3 O 4 by thermal decomposition, [6][7][8]20,22,23) chemical spray pyrolysis, 24) spattering, 25) and sol-gel process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, various transition metal oxides have been extensively studied over the past several years as oxidation catalysts because of their advantages including a lower price and adequate catalytic activities at relatively low temperature [3][4][5][6][7][8][9][10]. Among these metal oxides, Co 3 O 4 has attracted much attention due to its excellent catalytic performance in numerous reactions, e.g., the catalytic oxidation of CO, NO or VOCs as well as soot combustion [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…34 It was found that a small Co 3 O 4 -SiO 2 nanocomposite catalyst prepared using an activated carbon template exhibits very high activity for CO oxidation at À76 C.…”
mentioning
confidence: 99%